Short communication: Stocktaking forestry knowledge in Eastern Mediterranean: a glimpse on where do practitioners stand - Sattout, Elsa; Faour, Ghaleb; El Sarraf, Nadia (Forest Systems, 2017)
Aim of the study: To identify the lines of research initiatives and programmes on forest ecosystem and trees and shed lights on the need of new insights in forestry sector. Area of Study: Eastern Mediterranean countries (i.e. Jordan, Lebanon, Syria, Turkey). Materials and Methods: Online assessment through search on Google, Science Direct, Tandfonline, Forestry related journals, PLOS ONE, FAOSTAT, FAO-Agris, Unasylva, and Research Gate. Direct contacts were made with researchers at universities and professionals from international development organisations. Main results: The highest contribution in research is recorded in Turkey, followed by Lebanon, Syria and Jordan. Forest ecosystem functioning was ranked first in the research thematic areas, followed by forest ecosystem management. Research interest focuses on limited genera of coniferous and broadleaf trees. Emerging needs feature the execution of comprehensive national and regional stocktaking exercises to harmonize research agendas; ensuring synergies between international agreements’ goals (e.g. SDGs) and national policies instruments (e.g. NBSAPs); alignment of research agendas with national and international related frameworks; revisiting governance structure and regulatory measures and laws in the forestry sector. Research highlights: Insights put in the interface a new outlook on the leadership profile and foundation of interdisciplinary communities of practices. Rethink academic forestry related programmes and transform the approaches adopted to aim for more inclusiveness leading to stronger knowledge and coherent and successful practices in forestry.